Impact of the Charlson comorbidity index and prognostic nutritional index on prognosis in patients with early gastric cancer after endoscopic submucosal dissection. Issue 5 (11th April 2018) - Iwai, Naoto; Dohi, Osamu; Naito, Yuji; Inada, Yutaka; Fukui, Akifumi; Takayama, Shun; Ogita, Kazuyuki; Terasaki, Kei; Nakano, Takahiro; Ueda, Tomohiro; Okayama, Tetsuya; Yoshida, Naohisa; et al.
Abstract : Background and Aim: With the aging of society, comorbidities or nutritional status are assessed prior to endoscopic submucosal dissection (ESD) for early gastric cancer (EGC). However, it is uncertain which factors are important for predicting prognosis in EGC patients after ESD. Thus, we aimed to evaluate clinical outcomes of ESD for EGC, with respect to comorbidities or nutritional status. Methods: We carried out a retrospective study involving 708 EGC in 585 patients who were enrolled between April 2007 and March 2012. They were classified into two groups; an elderly (≥80 years) and non‐elderly (<80 years) group. Short‐ and long‐term outcomes were evaluated between the groups. Results: There were no significant differences regarding short‐term outcomes. Overall survival (OS) rates in the elderly group were significantly lower than those in the non‐elderly group ( P  =   0.001). OS rates in patients with a low (≤2) Charlson comorbidity index (CCI) were significantly higher than those in patients with a high (≥3) CCI, regardless of age. OS rates in patients with a high (≥47.7) prognostic nutritional index (PNI) were significantly higher than those in patients with a low (<47.7) PNI, regardless of age. In multivariate analysis, an Eastern Cooperative Oncology Group performance status (PS) ≥2 (hazard ratio [HR], 95% confidence interval: 3.23, 1.54–6.75), CCI ≥3 (HR 7.88, 4.50–13.80) and PNI <47.7 (HR 3.44, 2.00–5.90) were significantly associated with OS rate ( P  <   0.01). Conclusion: CCI and PNI can be prognostic indicators for non‐elderly and elderly patients with EGC after ESD.